THE RELATIONSHIP OF ANXIETY LEVELS WITH SLEEP QUALITY IN MEDICAL STUDENTS WHO ARE WORKING ON THESIS AT MULAWARMAN UNIVERSITY - Dwiana Sri palupi Teguh Saputri; Denny Jeffry Rotinsulu; Evi Fitriyani (Jurnal Ilmu Kesehatan, 2021)
Thesis is a scientific work to get a degree. Problems or difficulties in preparing thesis can cause anxiety to students. Excessive anxiety will have an impact on increasing tension and difficulty in starting sleep. This difficulty will interfere with students getting good sleep quality. This study aims to determine the relationship of anxiety levels with sleep quality in medical students who are working on thesis at Mulawarman University. This study was an observational analytic study with cross-sectional design. The research sample was 62 samples. Samples were selected by purposive sampling. Data collection uses the Zung Self-rating Anxiety Scale to assess anxiety levels and Pittsburgh Sleep Quality Index to assess sleep quality. The results of this study show that most students have mild anxiety level of 31 students (50%) and poor sleep quality of 43 students (69.4%). The analysis test using Spearman showed that anxiety levels was related with sleep quality (p = 0,000), the value of the level of closeness was very strong (r = 0.898). Based on the results of this study it can be concluded that there is a relationship between the level of anxiety with sleep quality in medical students who are working on thesis at Mulawarman University. Keywords: Anxiety Level, Sleep Quality, Thesis